Analisis Faktor-Faktor yang Berhubungan dengan Kejadian IMS pada Remaja di Klinik IMS Puskesmas Rijali dan Passo Kota Ambon - Jois Nari; Zahroh Shaluhiyah; Priyadi Nugraha Prabamurti (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTAnalysis of factors associated with the incidence of STIs adolescents in STIs Health center clinic Rijali and Passo Ambon City; Sexually transmitted infections are a serious problem in Indonesia as the disease continues to increase every year due to sexual behavior patterns among adolescents more freely. The purpose of this study was to analyze factors associated with the incidence of STIs in adolescents in STIs clinics and health centers Rijali and Passo Ambon City. This type of research is expalanatory research with cross sectional / prevalence study. The subjects of this study were teenagers who came for treatment, control and counseling at health centers and Passo Rijali with a sample size of 100 people. Data analysis was done by means of univariate, bivariate with Chi-square and multivariate logistic regression. Results of bivariate analysis of age and religiosity associated with risky sexual behavior while berisoko sexual behavior and history associated with the IMS IMS events. Results of logistic regression test showed a history of STIs are variables that most influence on the incidence of STIs in which teenagers who have a history of STIs, the possibility of risk for infection with STIs 31.4 times greater compared to teens who do not have a history of STIsKeywords : Sexually transmitted infections, adolescents